Changing Shape Design Materials Didactic Fractions in Primary Class IV - Heryasih, Mamay Enung; Herman, Tatang (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This study aims to develop a mathematical didactic design on the material to change the form of fractions in elementary school, in order to obtain optimal learning outcomes. Compilation is based barriers to learning that occurs in the learning process. The study was implemented in one of the main primary schools in Sumedang, the fourth grade students as research participants consisted of 37 students. The method used is the method of DDR (didactical Design Research) with a qualitative approach which the researchers themselves act as instruments. The activities in learning starts from the set trajectory learning didactic pedagogical hypothesis and anticipation. That students are exposed to practice solving problems related to the conversion of fractions and follows the daily life, so that students can solve their own problems that it faces. The results showed that the preparation of mathematics didactic design the material to change the form of fractions in elementary school, there are students' responses to learning. Most students can achieve learning objectives that have been defined, didactic design means it can reduce the difficulty of learning